"Laissez faire has had its day": Land Use, Waste, and Propertied Improvement in Early Canadian Planning. (20th October 2019) - Wideman, Trevor J.
ABSTRACT: Land use control has become a ubiquitous part of contemporary planning, but in early 20th century Canada such controls were under constant debate. I review these debates and interrogate planning-led anxieties around waste to show how planners used categories of waste to encourage land use control and to facilitate the improvement of people's lives and property. I think through the frictions that emerged when such planning ideas, mobilized through professional networks, touched down in the cities of Vancouver and Winnipeg. Land use regimes warrant increased scholarly attention: early conversations have contemporary relevance, as their discursive logics are foundational to modern methods of land use control.